Underage Marriage in Teenagers Judging from Law Number 16 of 2019 - Zetria Erma; Yulkarnaini Yulkarnaini (LEGAL BRIEF, 2022)
Marriage can be carried out by both men and women who are old enough. The purpose of this study is to identify and analyze the factors that cause underage marriage in Indonesia and underage marriage in adolescents in terms of Law Number 16 of 2019. This type of research is normative with a legal approach. The type of data used is secondary data consisting of primary, secondary and tertiary legal materials, while data analysis is carried out qualitatively. Factors that cause underage marriages in Indonesia are religion and culture, economy, education, already pregnant, the will of parents, their own will, customs and culture, feeling that they have been able to take responsibility, promiscuity, closing shame, arranged marriages, worship and social media. Meanwhile, underage marriages in adolescents according to Law Number 16 of 2019 are marriages carried out by boys and girls who are under the age of 19 (nineteen) years. In practice, it is mostly done by teenagers between the ages of 12 (twelve) to 19 (nineteen) years. This should not be done but if something unwanted happens and to protect the rights of children, especially girls, a marriage dispensation can be requested at the religious court.